Measurements of pp -> ZZ production cross sections and constraints on anomalous triple gauge couplings at root s=13 TeV - (:unkn) unknown (SPRINGER, 2021)
The production of Z boson pairs in proton-proton (pp) collisions, pp -> (Z/gamma*)(Z/gamma*) -> 2l2l', where l, l' = e or mu, is studied at a center-of-mass energy of 13 TeV with the CMS detector at the CERN LHC. The data sample corresponds to an integrated luminosity of 137 fb(-1), collected during 2016-2018. The ZZ production cross section, sigma(tot)(pp -> ZZ) = 17.4 +/- 0.3 (stat) +/- 0.5 (syst) +/- 0.4 (theo)+/- 0.3 (lumi) pb, measured for events with two pairs of opposite-sign, same-flavor leptons produced in the mass region 60 < m(l+l-) < 120 GeV is consistent with standard model predictions. Differential cross sections are also measured and agree with theoretical predictions. The invariant mass distribution of the four-lepton system is used to set limits on anomalous ZZZ and ZZ gamma couplings.